Implication of the Covid-19 Pandemic on the Governance of International Trade in the West Kalimantan's Entikong Border - Martoyo, Martoyo; Alunaza, Hardi; Ernianda, Annisa; Putri, Anggi; Mosquera Montoya, Maria Angela Lorena (Jurnal Manajemen Industri dan Logistik, 2022)
This paper is presented in response to the issue related to the impact of the COVID-19pandemic on the trade sector at the Entikong Border in West Kalimantan. The author uses cross-border governance to explain the dynamics and import-export activities during the pandemic. Data collection techniques in this study were interviews and literature studies. The results of this article show that export and import activities will continue during the pandemic. In 2020, it was found that freight shipments were recorded on both routes alone with 44.03% import-export activity through Supadio Airport amounting to US$193,668,243 and the Ports of Kendawang and Pontianak contributing 29.10%. In addition, there are oxygen import activities for pandemic mitigation and electricity imports to meet the needs of people at the border. During the pandemic, there was a change in international trade procedures impacted the depreciation of exports from Indonesia in early 2020 and started to stabilize in mid-April 2021. The Malaysian government's oxygen import policy took place as a result of the issue of increased oxygen demand during the Covid-19 pandemic. The activity of opening the two national borders between Indonesia and Malaysia can only be carried out for the importation of oxygen tanks (liquid oxygen), as well as the repatriation of PMI and the repatriation of motorized vehicles.